Biparatopic HER2-targeted nanobody binder synergizes with trastuzumab in resistant tumor cells - Liu, Xinlin; Guo, Li; Wang, Yihuan; Meng, Xiangzheng; Shao, Yunhan; Fan, Xinyi; Wang, Cong; Zhu, Wenjing; Cao, Jingyu; Sun, Peng (Frontiers in Immunology, 2025)
Human epidermal growth factor receptor 2 (HER2) is a key oncogenic driver in diverse solid tumors. Although HER2-targeted therapies such as trastuzumab and pertuzumab confer substantial clinical benefits, therapeutic resistance remains a major challenge, necessitating the development of next-generation agents. Here, we engineered a biparatopic nanobody-based binder, A9F5-H2F5-Fc (AH), designed to target ECD I and ECD II of HER2. In HER2-expressing tumor cells, AH induced greater receptor saturation, internalization, and degradation than the combination of trastuzumab and pertuzumab. Notably, in trastuzumab-resistant cancer cells, AH exhibited superior synergistic antitumor efficacy in combination with trastuzumab, outperforming trastuzumab plus pertuzumab. Structural modeling predicted a trans-binding mode that enables multivalent HER2 clustering, indicative of a distinct mechanism of action. These findings highlight AH as a rationally designed biparatopic binder with potential to overcome trastuzumab resistance and underscore the potential of nanobody-based biparatopic strategies to enhance antitumor efficacy in HER2-positive cancers.